Prediabetes in rural adolescent girls from DERVAN cohort: data from the KONKAN region of the state of Maharashtra, India (DERVAN-4) - Patil, Suvarna; Patil, Netaji; Hardikar-Bhat, Pallavi; Dervankar, Omkar; Joglekar, Charudatta; Bhat, Rohit; Nandoskar, Ajit; Yadav, Arvind; Nilawar, Anup (Frontiers in Public Health, 2023)
Background India is witnessing an epidemic of type 2 diabetes. Overweight/obesity, over nutrition, physical inactivity and family history are well known risk factors for diabetes. We investigated the role of undernutrition in the development of diabetes among rural adolescent girls. Methods DERVAN cohort study was set up in the KONKAN region of the Western Indian state of Maharashtra. It enrolled 1520 adolescent girls (16-18 years old at the time of enrollment). We measured glycemic parameters (glucose, insulin and HbA1C), body size by anthropometry and body composition by bioimpedance. Prediabetes was diagnosed using ADA criteria. We also calculated various HOMA indices for insulin resistance (HOMA-IR), 𝛽-cell function (HOMA-𝛽), insulin sensitivity (HOMA-S) and compensatory 𝛽-cell response using homeostasis model. BMI, body fat% and waist circumferences were treated as exposures and all the glycemic parameters and indices as outcomes. Results: Median age was 16.6 years. Median weight, height and BMI were 40.7 kg, 151.7 cm and 17.5 kg/m2 respectively. Prevalence of underweight was 28.8 % and stunting was observed in 30.4%. Thinness and obesity using BMI were observed in 58.4% and 4.2% respectively. Median body fat% was 22.5 and excess body fat (>35%) was observed in 5.7%. The prevalence of prediabetes was 39.4%. Fasting insulin concentrations, HOMA-IR and HOMA-𝛽 showed positive trend across body composition quartiles (p<0.001). HOMA-S and compensatory 𝛽-cell response showed inverse trend (p<0.001). Girls with prediabetes in the most undernourished group when compared with those in overweight/obese groups had lower median insulin concentrations (8.1 µIU/ml vs 17.1µIU/ml), lower HOMA-IR (1.1 vs 2.3) and lower HOMA-𝛽 (75.6 vs 129.2) but higher sensitivity (87.4 vs 43.7) (p <0.001) for all. Conclusions: We have reported high prevalence of prediabetes among rural adolescent girls with very low prevalence of obesity. Prediabetes in obesity is driven by hyperinsulinemia and overworking of pancreas while poor 𝛽-cell function and poor insulin secretion are major drivers in undernourished. The high-risk diabetes screening programs are much needed for the undernourished populations. A caution should be exercised for planning the interventions as overfeeding (or overnutrition) is likely to put the populations at risk of development of obesity and insulin resistance.